ChemInform Abstract: Aryl Sulfonates in Inversions at Secondary Carbohydrate Hydroxyl Groups: A New and Improved Route Toward 3‐Azido‐3‐deoxy‐β‐D‐galactopyranosides. Issue 17 (April 2016) - Peterson, Kristoffer; Weymouth‐Wilson, Alex; Nilsson, Ulf J.
Abstract: A new method of using benzenesulfonates and imidazylates as leaving groups at the secondary C3 galactopyranose carbon, instead of the commonly used less stable triflate leaving group is developed to afford an improved and robust route toward the title compounds.